PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN EDUWISATA DI KK26 DALAM MENDUKUNG DESA OLEAN MENJADI WISATA UNGGULAN DI KABUPATEN SITUBONDO - Nurul Avidhah Elhany; Desi Indriyani; Nuris Hidayat; Shinta Nuriya Prayudi; Rike Andika Aris Susanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Universitas Abdurachman Saleh Situbondo, 2025)
Edutourism is an effort to increase new knowledge through tourism activities. Educational and recreational tourism activities should be a means of socializing and fostering a sense of pride and love for culture and nation. The purpose of this activity is to provide training and mentoring on educational tourism for KK26 managers so that they can develop tourist destinations into educational and recreational tourism that is busy with visitors so that it can improve the economy of the village community. This PKM program is implemented at KK26 Tourism, Olean Village, Situbondo Regency. The implementation period of this PKM program starts from June 2025-August 2025. The target of this PKM program is the KK26 tourism management group, Olean Village, Situbondo. The method of implementing the community service consists of several stages, namely activity socialization, edutourism program training and marketing training on social media. The training and mentoring activities of the edutourism program at KK26, Olean Village, Situbondo Regency were very well received by partners, this is evidenced by the very high involvement and active participation of partners in the implementation of the program. The educational tourism training program provided included seedling planting for kindergarten and elementary school children and the benefits of each plant. Based on monitoring and evaluation results, partners have acquired the knowledge and skills to create the products taught.